Clinical significance of Helicobacter pylori cagA and iceA genotype status - Mohammad Amjad, Nasser; Osman, Hussain Ali; Abdul Razak, Najibah; Kassian, Junaini; Din, Jeffri; Abdullah, Nasuruddin (Baishideng Publishing Group, 2010)
AIM: To study the presence of Helicobacter pylori (H. pylori) virulence factors and clinical outcome in H. pylori infected patients. METHODS: A prospective analysis of ninety nine H. pylori-positive patients who underwent endoscopy in our Endoscopy suite were included in this study. DNA was isolated from antral biopsy samples and the presence of cagA, iceA, and iceA2 genotypes were determined by polymerase chain reaction and a reverse hybridization technique. Screening for H. pylori infection was performed in all patients using the rapid urease test (CLO-Test). RESULTS: From a total of 326 patients who underwent endoscopy for upper gastrointestinal symptoms, 99 patients were determined to be H. pylori-positive. Peptic ulceration was seen in 33 patients (33%). The main virulence strain observed in this cohort was the cagA gene isolated in 43 patients. cagA was associated with peptic ulcer pathology in 39.5% (17/43) and in 28% (16/56) of non-ulcer patients. IceA1 was present in 29 patients (29%) and iceA2 in 15 patients (15%). Ulcer pathology was seen in 39% (11/29) of patients with iceA1, while 31% (22/70) had normal findings. The corresponding values for iceA2 were 33% (5/15) and 33% (28/84), respectively. CONCLUSION: Virulence factors were not common in our cohort. The incidence of factors cagA, iceA1 and iceA2 were very low although variations were noted in different ethnic groups.